INFORMATION-ANALYTICAL PROVISION OF FINANCIAL SECURITY OF INDUSTRIAL ENTERPRISES: DETERMINANTS, EVALUATION OF INDICATORS AND MECHANISMS OF STRENGTH - VIVCHAR, OKSANA; KRZYWKOWSKA, JUSTYNA; MYKHAILYSHYN, LILIIA; KOHUT-FERENS , OKSANA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
Conceptual aspects of industrial enterprises financial security are considered, features of industrial enterprises financial security information and analytical support functioning are determined. On the basis of which a structural and logical scheme of information and analytical support of an industrial enterprise financial security in modern transformational conditions is proposed. The analysis of the current state of major external and internal threats identification is carried out. Based on the results of the analysis, it was found that the most risky components of an industrial enterprise financial security are investment and credit, since these components carry the greatest number of risks. Also, a comprehensive analytical assessment of the information and analytical support formation of the country’s Western region business structures financial security was made. The calculations make it possible to identify the main problematic aspects of the functioning of enterprises and threats to their financial security and to develop measures to strengthen it. The economic efficiency of the information and analytical support system introduction of industrial enterprises financial security with consideration of strategic and tactical vectors of development, and also depends on completeness, reliability, timeliness of the information component. The algorithm of forming information and analytical support of industrial enterprises financial security assessment with consideration of software is investigated. On the basis of which a multi-vector mechanism of information and analytical support of industrial enterprises financial security in modern conditions of turbulence of economic processes is proposed. This will make the decision-makers informed, both strategic and tactical, operational.